Are the subsidies to private capital useful? A Multiple Regression Discontinuity Design Approach1 - Guido Pellegrini; Augusto Cerqua (European Regional Science Association (ERSA), 2011)
There is still little consensus on the effectiveness of business support policies. The empirical evaluation is complicated by the difficulty in achieving reliable identification. We analyse the impact of Law 488/92, the main Italian regional policy. We propose a new approach, named multiple regression discontinuity design that exploits the sharp discontinuities in the L488 rankings and extends the RDD approach to a context where the treatment is assigned by multiple rankings with different cut-off points. We find that the impact of L488 on investment and production of the financed firms is positive and statistically significant.
Keywords: 330